2011
DOI: 10.1002/cpp.698
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality and posttraumatic stress disorder in victims of violence: a cross‐sectional exploration

Abstract: The current study explored the relationship between type D personality and posttraumatic stress disorder (PTSD) among victims of violence (n = 189). The basic premise underlying the type D concept is that it is not the experience of negative emotions per se that renders individuals at risk of maladjustment in the face of adversity, but the way they are dealt with. Particularly the combination of high negative affectivity and social inhibition (i.e., the non-expression of emotions and inhibition of behaviours i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 63 publications
0
13
0
1
Order By: Relevance
“…This is consistent with the results of a systematic review [31] that indicated the presence of a Type D personality had a negative impact on mental health status including PTSD. Kunst et al [12] also observed Type D personality in violence victims predicted their PTSD. Type D personality is characterized by a combination of negative affectivity and social inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of a systematic review [31] that indicated the presence of a Type D personality had a negative impact on mental health status including PTSD. Kunst et al [12] also observed Type D personality in violence victims predicted their PTSD. Type D personality is characterized by a combination of negative affectivity and social inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of Type D personality among clinical nurses is higher than that of general population, reaching at 36–38%, and nurses with Type D personality experience more compassion fatigue, burnout, and job stress than those with non-Type D personality [10, 11]. Previous studies have observed that Type D personality was positively correlated with PTSD in a group of violence victims [12] and firefighters [13]. …”
Section: Introductionmentioning
confidence: 99%
“…A number of potential risk factors of PTSD have been identified in previous trauma research, including family history of psychiatric disorders, childhood trauma, depression, female gender (Breslau, 2002;Brewin, Andrews, & Valentin, 2000;von Känel, Baumert, Kolb, Cho, & Ladwig, 2011), and personality (Kunst, Bogaerts, & Winkel, 2010;Mommersteeg et al, 2011). Type D (distressed) personality (i.e., evidenced by a tendency to experience negative emotions and to inhibit self-expression) has been indicated as an independent predictor of PTSD after a myocardial infarction (Chung, Berger, & Rudd, 2007;Pedersen & Denollet, 2004).…”
mentioning
confidence: 99%
“…Items need to be answered on a 5-point Likert scale ranging from 0 (false) to 4 (true). In accordance with previous victim studies (Kunst et al 2009, 2011), a pre-determined cut-off score of ≥10 on both subscales was used to classify participants as type D. Emons et al 2007 have shown that the DS14 items have the highest measurement precision around this cut off. The subscales of the DS14 have high internal consistency and good test-retest validity over a three-month period (Denollet 2005).…”
Section: Methodsmentioning
confidence: 95%